INFLUENCE OF SALINITY ON UPTAKE RATE AND BIOACCUMULATION OF 137Cs IN THE OYSTER CRASSOSTREA GLOMERATA - Mashiatullah, A.; Qureshi, R. M.; Khan, S.; Abid, J.; Javed, T.; Chughtai, F.; Akhtar, P.; Jabbar, A. (The Nucleus, 2020)
This paper describes results of experiment on bioaccumulation and uptake rate of radiocesium 137Cs from dissolved phase in the flesh of the Oysters (Crassostrea glomerata) collected off Karachi coast. A radiotracer experiment was conducted under laboratory conditions to determine the uptake rate and bioaccumulation of 137Cs from dissolved phase in the flesh of the Oysters. Oysters (size: 6–7 cm) were subjected to radiocesium activity of 24 Kilobecquerel per liter (kBq L-1) under three salinity levels (25, 30 and 35 ppt). The uptake of 137Cs was monitored for a period of seven days. The results showed that bioaccumulation and uptake of 137Cs in oysters were considerably dependent of salinity levels. Higher bioaccumulation factors and uptake rates were found at low salinity levels.